PENYELENGGARAAN KETENAGAKERJAAN OLEH DINAS TENAGA KERJA KABUPATEN ROKAN HILIR TAHUN 2015 – 2017 - Wan Nazarudin; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is based on the fact that the unemployment rate in the downstream rokan district increases every year. This is due to the economy, thinking and nature of job seekers, low education. This study aims to determine employment by the downstream district of labor offices. this research uses descriptive method with qualitative approach, observation, interview and documentation. The technique of collecting research subjects is by using purposive sampling technique, from this technique obtained key infoman, which consists of heads of information on labor distribution and training, head of labor inspection, head of industrial sector, head of labor distribution, head of personnel training section work, staff in the field of labor supervision. 1 Member of Rokan Hilir Regency DPRD, 1 person training in labor. Observations, interviews and documentation are data collection techniques conducted by researchers. the results of the research conducted through interviews and field observations and then analyzed can be concluded that the employment of the downstream Regency Manpower Office in the Category has been sufficiently optimal, for reasons including the Rokan Hilir District Manpower Office only implementing 6 activities or 6 indicators from 11 activities or 11 research indicators according to Rokan Hilir District Regulation No. 8 of 2014 concerning Managing employment and employment services must optimize the implementation of the labor market and online exchanges and for the government parties must carry out more frequent training in labor, and communicate with the private sector or companies to establish good relations. Keywords: Organization, Employment, role